Implementing a standardized screening protocol for parental depression, anxiety, and PTSD symptoms in the Neonatal Intensive Care Unit. (March 2021) - Moreyra, Angelica; Dowtin, LaTrice L.; Ocampo, Maria; Perez, Emily; Borkovi, Tonyanna C.; Wharton, Emily; Simon, Stephanie; Armer, Erin G.; Shaw, Richard J.
Abstract: The aim of this paper is to describe the development of a standardized screening program for parents of infants in the Neonatal Intensive Care Unit (NICU) and to assess its implementation. The standardized screening protocol assessed parental mental health symptoms including depression, anxiety and trauma. Screening began at 14 days post NICU admission and was implemented as part of routine medical care for all caregivers with infants admitted to the NICU at two weeks of age. Screenings were facilitated by pediatric social workers and psychology postdoctoral fellows and included review of critical self-harm items. A total of 158 parents ages 18–42 years (mean = 31.04) were eligible for screening, with 150 completed screenings. Positive screens on any of the three measures resulted in a mental health referral. Approximately 27% of parents had a positive screen that resulted in a mental health referral. The standardized screening protocol was found to be feasible, widely accepted, and effective in establishing referrals for in house mental health services. This model can be used as an example to help other NICUs implement their own universal screening protocols.